A Downward Trend of the Ratio of Influenza RNA Copy Number to Infectious Viral Titer in Hospitalized Influenza A-Infected Patients. (3rd November 2015) - Van Wesenbeeck, Liesbeth; D'Haese, David; Tolboom, Jeroen; Meeuws, Hanne; Dwyer, Dominic E.; Holmes, Mark; Ison, Michael G.; Katz, Kevin; McGeer, Allison; Sadoff, Jerald; Weverling, Gerrit Jan; Stuyver, Lieven
Abstract: Background.  Efficacy endpoints in influenza clinical trials may include clinical symptoms and virological measurements, although virology cannot serve as the primary endpoint. We investigated the relationship between influenza A RNA copy number and quantity of infectious viruses in hospitalized influenza patients. Methods.  One hundred fifty influenza-infected, hospitalized patients were included in this prospective cohort study spanning the 2012–2013 influenza season. Daily nasopharyngeal samples were collected during hospitalization, and influenza A RNA copy number and infectious viral titer were monitored. Results.  The decay rate for 50% tissue culture infectious dose (TCID50 ) was 0.51 ± 0.14 log10 TCID50 /mL per day, whereas the RNA copy number decreased at a rate of 0.41 ± 0.04 log10 copies/mL per day (n = 433). The log ratio of the RNA copy number to the infectious viral titer within patient changes significantly with −0.25 ± 0.09 units per day ( P = .0069). For a 12-day observation period, the decay corresponds to a decline of this ratio of 3 log influenza RNA copies. Conclusions.  Influenza RNA copy number in nasal swabs is co-linear with culture, although the rate of decay of cell culture-based viral titers was faster than that observed with molecular methods. The study documented a clear decreasing log ratio of the RNA copy number to the infectious viral titer of the patients over time.